Ionic liquids for addressing unmet needs in healthcare - Agatemor, Christian (Bioeng Transl Med, 2018)
Advances in the field of ionic liquids have opened new applications beyond their traditional use as solvents into other fields especially healthcare. The broad chemical space, rich with structurally diverse ions, and coupled with the flexibility to form complementary ion pairs enables task‐specific optimization at the molecular level to design ionic liquids for envisioned functions. Consequently, ionic liquids now are tailored as innovative solutions to address many problems in medicine. To date, ionic liquids have been designed to promote dissolution of poorly soluble drugs and disrupt physiological barriers to transport drugs to targeted sites. Also, their antimicrobial activity has been demonstrated and could be exploited to prevent and treat infectious diseases. Metal‐containing ionic liquids have also been designed and offer unique features due to incorporation of metals. Here, we review application‐driven investigations of ionic liquids in medicine with respect to current status and future potential.